Efficacy of fenugreek plant for ascorbic acid assisted phytoextraction of copper (Cu); A detailed study of Cu induced morpho-physiological and biochemical alterations. (July 2020) - Fatima, Arooj; Farid, Mujahid; Alharby, Hesham F.; Bamagoos, Atif A.; Rizwan, Muhammad; Ali, Shafaqat
Abstract: Phytoremediation via phyto-extraction is well recognized and sustainable principle for the economical removal of heavy metals from contaminated water and soil. The twofold objective of the present research work was to investigate the remediation potential of fenugreek for Cu under the influence of ascorbic acid (AA). The effect of copper-ascorbic acid chelation on the growth regulation of fenugreek ( Trigonella foenum-graceum L.) and its potential to accumulate Cu was investigated in hydroponic medium to optimize concentration with complete randomized design (CRD). Juvenile fenugreek plants were treated with different treatments of AA (5 mM) and Cu (100, 250 and 500 μM). The different morpho-physiological parameters of fenugreek plant such as growth, biomass and chlorophylls were significantly reduced under Cu stress. However, the activities of antioxidant enzymes, electrolyte leakage and reactive oxygen species enhanced with increasing concentration of applied Cu. Results indicated significant increase in plant growth, biomass, physiology and antioxidant enzymes and decrease in reactive oxygen species and electrolyte production in AA mediated fenugreek plants compared to controls and Cu only treated plants. However, it was also found that AA enhanced Cu concentration maximum up to 42% in leaf, 18% in stem and 45% in roots as compared to Cu treated only plants. Moreover, application of AA signified the research results revealing to act as growth regulator and chelator under Cu stress. Graphical abstract: Image 1 Highlights: Copper stress altered biochemical functions and reduced agronomic traits. Ascorbic acid improved photosynthetic pigments and antioxidant defense system. Ascorbic acid enhanced growth and biomass of plant by increasing nutrient uptake. Ascorbic acid enhanced bioavailability of Cu in media and uptake in plant.